Prinsip Pembelajaran dalam Kurikulum Merdeka - Muhamad Damiati; Nurasikin Junaedi; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this study is to explore and discuss the principles and ways of learning in the independent curriculum. whether the way of learning that we carry out is correct or in accordance with the Independent Curriculum or is it still with the old pattern, and the government changes the curriculum to the Merdeka curriculum, this is not just a project not just a name change but the government really wants to improve the education system in Indonesia according to the times and also the evaluation carried out by the government. In this study report, the method used is a descriptive qualitative method by taking notes because the source of the data obtained by listening to the oral narrative from the Young Teacher's Note Youtube channel entitled " How to Teach in the Independent Curriculum, Learning Principles of the Independent Curriculum " presented by him. The results showed that the implementation of the independent curriculum requires the readiness of school principals and teachers to learn new things. In the planning process, teachers still rely on teaching modules provided by the center. There are new things that must be considered in the independent curriculum with the project of strengthening the profile of Pancasila students. The implications of this research are expected that teachers can use the 11st century learning model in the application of the independent learning curriculum in schools